EFFECT OF NESTING ON PHYSIOLOGICAL PARAMETERS AMONG PRETERM BABIES ADMITTED IN NICU - Mrs. Krishnaja M Unnikrishnan, Aneesha V B, (Chelonian Research Foundation, 2023)
The present study is aimed to determine the effect of nesting on physiological parameters among preterm babies admitted in NICU of Amala Institute of Medical Sciences, Thrissur. Objectives are to analyze the physiological parameters among preterm babies, determine the effect of nesting on physiological parameters among preterm babies and also to find the association between physiological parameters with baseline variables. The research approach is quantitative approach and research design is cross over design. The study is based on Ludwig Von Bertalanffy, general system model. Twenty preterm babies were selected by purposive sampling technique.Samples were randomly allocated for nesting and routine care. Tools used were structured questionnaire to determine the baseline variables and physiological parameter data sheet to record physiological parameters after nesting and routine care. The calculated ‘t’ value and p value of heart rate is 0.26 and 0.797 respectively, respiratory rate is 0.163 and 0.109, temperature is 0.113 and 0.910 and oxygen saturation is 2.74 and 0.009 respectively after nesting and routine care. Hencethe‘t’ value of oxygen saturation is statistically highly significant at 0.05 level irrespective of other physiological parameters that are maintained stable and showed differences but statistically not significant after nesting and routine care. The study findings depicts that, heart rate and respiratory rate were decreased, mean body temperature was increased but statistically not significant after nesting as compared to routine care. The study findings reveals that nesting is effective in sustaining stable physiological parameters among preterm babies. Key words:nesting, physiological parameters, preterm babies, data sheet to record physiological parameters.